Meningkatkan Hasil Belajar Matematika Pada Materi Statistika Dengan Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Pada Siswa Kelas V SD - Setiadi, Belly (Jurnal Pendidikan Tuntas, 2025)
This research is motivated by the low mathematics learning outcomes of fifth-grade students at SD Negeri 005 Bukit Kapur, Dumai City, specifically in Statistics material. The main problem identified is the conventional learning process, which leads to low concentration, lack of activity, and low student motivation towards mathematics, which is often perceived as a difficult subject. The primary objective of this study is to describe how the implementation of the Numbered Head Together (NHT) cooperative learning model can improve learning outcomes and students' active engagement in the learning process. The research method employed is Classroom Action Research (CAR), conducted in two cycles, where each cycle includes the stages of planning, implementation, observation, and reflection. Data collection techniques were carried out through observations of teacher and student activities as well as learning outcome tests at the end of each cycle. The research results show a significant increase in students' learning completeness. In Cycle I, the percentage of student learning completeness only reached 60%, but after corrective actions were taken in Cycle II, the percentage increased drastically to 90%, representing a 30% improvement. In addition to the increase in cognitive scores, the implementation of the NHT model also proved capable of increasing student concentration because each individual has responsibility for the number they hold. Students became more enthusiastic in group discussions, more confident in expressing opinions, and mastery of the material became deeper through collaboration between group members. The NHT model successfully created a more dynamic and healthily competitive classroom atmosphere. In conclusion, the NHT type cooperative learning model is highly effective in improving mathematics learning outcomes in Statistics for elementary school students. The researcher recommends the use of this model as an alternative learning strategy to increase students' active participation in the classroom.